PWE-028 Persistence of biologic therapy and mapping of sequential biologics: results of a single centre cohort. (8th June 2018) - Jenkinson, Philip; Plevris, Nik; Chuah, Cher Siong; Lyons, Mathew; Merchant, Lynne; Jones, Gareth; Arnott, Ian; Lees, Charlie
Abstract : Background: Biologic therapy has revolutionised the treatment of IBD in the last 20 years. There is limited data on the patient journey through multiple lines of biologics and mapping this to outcomes. We aimed to establish the prevalence of biologic use in a single tertiary IBD centre and assess outcomes defined by biologic persistence. Methods: Retrospective review of electronic health records (TrakCare) was performed on all patients who have received infliximab (IFX), adalimumab (ADA), vedolizumab (VEDO) or ustekinumab (UST) in Edinburgh from January 1999 to October 2017. We collected data for demographics, phenotyping details and duration of treatment. Kaplan–Meier survival curves and log-rank analyses were used to compare time to either discontinuation or resectional surgery. Result: 841 patients were identified who have had biologic therapy for IBD. Median interval from diagnosis to biologic was 4.9 years (IQR 1.3–11.0). The multiple combinations of biologics used is displayed in Figure 1. 665 CD patients (79.7% of total) were treated with biologics; 486 received IFX (73.1%), 169 ADA (25.4%) and 10 VEDO (1.6%) as first line therapy. Second line therapy was required in 238 patients and consisted of ADA 189 (79.4%), IFX 25 (10.9%), VEDO 18 (7.6%) and UST 6 (2.5%). Third line therapy was required in 57 patients, VEDO 41 (74.5%) and UST 14 (25.5%). 3 (0.5%) patients received fourth line therapy with UST. In the CD cohort persistence of treatment on ADA was longer than IFX when used as first line treatment; median 2373 vs 1430 days (p=0.0189). Conclusion: Multiple sequential biologic use is becoming increasingly common and this will accelerate with the increasing use of anti-integrin and anti-IL12/IL23 therapies. Mapping the sequence of biologic use and linking this to outcomes is a priority for IBD research.